Arbuscular mycorrhizal association with important medicinal plants of Sagar+ - and DEEPAK VYAS*, PRASHANT KUMAR SONI (Indian Phytopathology, 2007)
Five medicinal plants viz. Ocimum sanctum, Mentha arvensis, Centella asiatica, Oxalis corniculata and Acorus calamus, belonging to four different families such as Lamiaceae, Apiaceae, Oxalidaceae and Araceae were studied for their Arbuscular Mycorrhizal (AM) association. All the test plants were growing in the Botanical Garden of Dr. H.S. Gour University, Sagar (M.P.). The result revealed that all the five medicinal plants had AM association in the roots and spore population in the rhizospheric soil. However, percent root colonization, spore population and AMF species varied from plant to plant. Maximum percent root colonization and spore population of AM fungi was observed in Ocimum sanctum followed by Centella asiatica, Mentha arvensis and Oxalis corniculata, whereas minimum root colonization and spore population was observed in Acorus calamus. Total 14 AMF species were identified and quantified in which Glomus spp. were found dominate followed by Acaulospora spp. and Sclerocystis spp. Gigaspora spp. were found poorly distributed.